Pengaruh Berbagai Jenis Media Perkecambahan Terhadap Vigor Benih Kakao (Theobroma Cacao L.) Varietas Bl50 - Nike Karjunita; Kuswandi (Jurnal Riset Perkebunan, 2022)
Cocoa is one of the plantation commodities which is a source of state income. Growing media is not only related to seed germination in general, but also relates to the ability of seeds to survive even in a less favorable environment. The purpose of this study was to determine the vigor of cocoa seeds of BL50 variety on several types of germination media. The research was carried out in Nagari Tanjung Lolo, Tanjung Gadang District, Sijunjung Regency from March to April 2022. The tools used consisted of a handsprayer, ruler, caliper, and writing utensil. The materials used in this experiment were BL50 variety cocoa seeds, crushed bricks, humus soil, sand, and insecticide. The experiment was arranged according to the rules of Randomized Block Design (CRD) with 3 treatments and 4 replications, and each replication consisted of 7 samples, with a total of 84 samples of cocoa seeds. The treatments given in this study were various sprout media, namely; A = crushed brick B = humus soil, and C = sand. The data were analyzed for variance, if significantly different, it was continued with the Honestly Significant Difference Test (BNJ). The results showed that humus soil media was a good medium for accelerating germination, while sand media was good for root development which included root length and diameter.